Risk management with HACCP - Yeung, Mylene A. (Manila, Philippines : Edric Publishing House, 2019)
This book, Risk Management with HACCP is intended as a reference for students enrolled in Hospitality and Tourism related disciplines. The book was written in line with prescribed contents of course in Risk management as applied to Safety, Security and Sanitation. The book is made up often (IO) chapters. Principles of Food Safety and Sanitation was extensively discussed in chapter I. Methodical discussion on risk management has been emphasized in Chapter 2. Food and occupational Safety Hazards were presented in chapters 3 and 4 respectively. Chapter 5 contains topics on kitchen safety. Chapters 6 and 7 was about Foodhandlers and workplace Hygiene. A comprehensive discussion on Food flow in Chapter 8 followed by a presentation on a food protection system called hazard analysis critical control points were made in chapter 9. Finally, information about food safety plan was made in Chapter I 0. The pedagogical features included in this book will help students, faculty members, and others maximize the value of this text and foster more positive learning outcomes. Exercises at the end of each chapter to help pinpoint the important concepts of the subject matter and serve as a study review and test for the reader, ensuring more important information is learned. F ood safety and sanitation is an indispensable part of the food service industry. Ensuring safe food is an important public health priority. Food sanitation is more than just cleanliness. It includes all practices involved in protecting food from risk of contamination, harmful bacteria, poisons and foreign bodies. The word sanitation is derived from the Latin word sanitas, meaning "health." Applied to tha food industry, sanitation is "the creation and maintenance of hygienic and healthful conditions." It is the application of a science to provide wholesome food processed, prepared, merchandised, and sold in a clean environment by healthy workers to prevent contamination with microorganisms that cause food bomeillness, and to minimize the proliferation of food spoilage microorganisms. Effective sanitation refers to all the procedures that help accomplish these goals.
PRINCIPLES OF FOOD SAFETY AND SANITATION -- Sanitation - Food Hygiene - Food Suitability - Food Safety - 'Food Security - Laws Relating to Health and Safety - Regulatory Agency -- CHAPTER 2 RISK MANAGEMENT -- Risk Analysis - Risk Assessment - Risk Management - Elements of Risk Management - General Principles of Food Safety Risk Management - Risk Communication -- CHAPTER 3 FOOD SAFETY HAZARDS -- Physical Hazards - Chemical Hazards - Biological Hazards - Sources of Food Safety Hazards - Food Poisoning - Food-borne Disease - Potentially Hazardous Foods -- CHAPTER 4 OCCUPATIONAL SAFETY HAZARDS IN FOOD OPERATIONS -- Hazard Identification and Risk Control 28 - Solutions for Hazards in Food Service 29 - Fire Hazard 34 - Ergonomics Reduces Injuries 37 - Workplace Violence 38 - SERVICE 27 -- CHAPTER 5 KITCHEN SAFETY: PRECAUTIONS AND FIRST -- AID 45 - First Aid for Kitchen Accidents. 45 - Basic First Aid Kit Contents 45 - First Aid for Common Kitchen Accidents 46 - CHAPTER 6 FOOD HANDLER'S SAFETY AND HYGIENE 57 - Healthy Food Handler 58 - Personal Health Habits - Handwashing Basics - CHAPTER 7 WORKPLACE HYGIENE - Cleaning and Sanitizing Program 71 - Fundamentals Cleaning Procedure 72 - Factors Influencing Cleaning 74 - Methods of Cleaning 75 - Rinsing 78 - Sanitizing Principles 78 - General Types of Sanitization 78 - Factors Affecting Sanitizer Effectiveness 81 - Manual and Mechanical Ware Washing 82 - Pests in Food Service Facility 83 - Types of Waste Hospitality and Food Service Operations 85 - Solid Waste Disposal Systems 85 - Sanitary Liquid Waste Disposal 86 -- CHAPTER 8 FOOD FLOW -- The Food Product Flow -- Purchasing - Receiving - Proper Storage - Thawing Food - Preparation of Safe Food - Cooking Food - Cooking Guidelines - Holding Food - Cooling Food - Service of Food - Reheating Food - Food Packaging -- CHAPTER 9 HAZARD ANALYSIS AND CRITICAL CONTROL POINT 115 -- Definitions 115 - History 116 - Advantages 116 - HACCP Highlights 117 - Benefits of a HACCP based Food Safety Management System 118 - Developing a HACCP Plan 119 -- CHAPTER IO FOOD SAFETY PLAN 125 -- Implementation a Food Safety Plan - Preventive Measures and Control Limits - Application o f Food Safety Plan - Bibliography.
Includes bibliographical references.
Keywords: FOOD -- SAFETY MEASURES